Symposium 5: How can Networked Learning promote student-directed learning at AUT? - Winters, Annemie; Chanane, Nawal; Eberhard, Sally; Kehrwald, Benjamin; Nguyen, Nhung; Sim, Kwong Nui (Proceedings of the International Conference on Networked Learning, 2024)
Auckland University of Technology (AUT) is a young university in Aotearoa New Zealand, focusing on the student experience. This paper looks at the learning environment in that context and questions where networked learning principles could contribute to the strategic goal of student-directed learning. The paper explores central notions in networked learning as strengths and weaknesses, and redefines student-directed learning for the context of AUT.